Recurrent Myalgia since Early Infancy—Misleading Clinical Course in a Child with Carnitine Palmitoyltransferase-II Deficiency - Arélin, Maria; Zierz, Stephan; Ceglarek, Uta; Heinemann, Mitja; Beblo, Skadi; Merkenschlager, Andreas (Neuropediatrics, 2020)
Metabolic myopathies are heterogeneous hereditary diseases affecting skeletal muscle energy supply. Symptoms usually comprise pain, cramps, hypotonia, weakness, and myoglobinuria.We present a boy with recurrent myalgia and weakness after some minutes of exercise or during febrile infections since early infancy. First laboratory workup at the age of 9 years showed no abnormalities, apart from a slightly elevated creatine kinase. After exclusion of common structural and metabolic myopathies, next generation sequencing panel (4 years after the initial diagnostic metabolic workup) revealed two potentially pathogenic missense mutations in the CPT2 gene (c.149C > A (p.P50H) and c.1459G > A (p.E487K)).Our case underscores the clinical variability of muscle carnitine palmitoyltransferase II (CPT II) deficiency and illustrates a pitfall of diagnostic algorithms for metabolic myopathies. Myalgia following exercise of a few minutes duration would have argued for a carbohydrate and against a fatty acid metabolic defect. However, CPT II deficiency is the most common disorder of muscle fatty acid metabolism and should be considered even in atypical scenarios. Analyses of plasma acyl carnitine profile during acute metabolic crises may help to unmask biochemical markers which are often overlooked in dried-blood analyses.
Keywords: acute/recurrent myalgia; metabolic myopathies; carnitine palmitoyltransferase II deficiency